The Routledge Companion to Early Christian Thought. - Bingham, D. Jeffrey (Routledge companions., 2009)
The shape and course which Christian thought has taken over its history is largely due to the contributions of individuals and communities in the second and third centuries. Bringing together a remarkable team of distinguished scholars, The Routledge Companion to Early Christian Thought is the ideal companion for those seeking to understand the way in which Early Christian thought developed within its broader cultural milieu and was communicated through its literature, especially as it was directed toward theological concerns. Divided into three parts, the Companion: asks how Christianity's development was impacted by its interaction with cultural, philosophical, and religious elements within the broader context of the second and third centuries. examines the way in which Early Christian thought was manifest in key individuals and literature in these centuries. analyses Early Christian thought as it was directed toward theological concerns such as God, Christ, Redemption, Scripture, and the community and its worship.